Host diversity of Aedes albopictus in relation to invasion history: a meta-analysis of blood-feeding studies - László Zsolt Garamszegi (Parasites & Vectors, 2024)
Abstract Background The invasive mosquito Aedes albopictus is a major concern for human and animal health given its high potential to spread over large geographical distances, adapt to various habitats and food sources, and act as a vector for pathogens. It is crucial to understand how this species establishes ecological relationships at different locations, as it determines its role in transmission of diseases. Methods Based on published blood meal surveys, a meta-analysis was performed to investigate how host diversity changes along the process of invasion at a large scale. For 48 independent localities, the Shannon diversity index was calculated and was then assessed against several moderator variables describing invasion status, habitat type, methodology, survey year and the year of introduction for invasive populations. Results Diet diversity was higher in the invasive than in the native populations when the strong habitat effects were held constant. Furthermore, the year of introduction also had a significant role, as invasive populations that had been established earlier had wider diet diversity than more recent populations. Conclusions Invasive Ae. albopictus has considerable ecological flexibility. The species’ ability to adapt to various food sources goes hand in hand with its successful worldwide dispersion, which has strong implications for its role in pathogen transmission. Graphical Abstract